Gardens of Delight, or What's Cookin'? Leonora Carrington in the Kitchen - Sonia Assa (Studies in 20th & 21st Century Literature, 1991)
Most of the short stories written between the years 1937 and 1941 by Leonora Carrington, a Surrealist painter and story-teller, are centered around an eating scene: "une scène" and/or "cène." Few of her stories fail to include an allusion to eating, and more often to devouring, while the food in question is seldom "innocent." The experience of the body or "corps propre" as represented in her narratives, is that of a body eating/being eaten, a place of culinary alchemies which is also manipulated, or manipulates itself, in order to exercise control over the outside world. In this fictional realm dominated by magic, perversion and anarchic excess, food elaboration and food consumption are posited as the central act of the narrative. A fascination with the abject and a willingness to provoke her readers' disgust in a language that is marked by the extreme nimbleness of phobic speech, seem to me to offer the clue to Carrington's fiction. That her "oral center," the appetite as/and voice should be the place of writing, reveals the distinctive femininity of her inspiration. For, as many historical, anthropological and psychological studies have suggested, women use appetite as a form of expression more often than men. Rather than "dis-moi qui tu hantes," I will therefore ask "dis-moi ce que tu manges," hoping to found out "ce que tu es."
Keywords: Leonora Carrington; Surrealism; surrealist artists; une scène; cène; food; indulgence; corps propre; control; magic; excess; consumption; appetite; femininity